Psychoanalyzing the Left and Right after Donald Trump Conservatism, Liberalism, and Neoliberal Populisms - Samuels, Robert (Critical Theory and Practice in Psychology and the Human Sciences, 2016)
This book outlines a new model for global social justice movements that is based on Freud and Lacan's central insights regarding the unconscious, repetition, drives, and transference. Since most of our current social issues are global in nature, Bob Samuels convincingly argues that we need a global solution, but that global solidarity is blocked by narcissistic nationalism and the capitalist death drive. In examining contemporary social movements for global justice, Samuels articulates a comprehensive theory of non-pathological social solidarity, and argues that in the age of multinational corporations and global climate change, we need a new model of global justice and government that requires an understanding of analytic neutrality and free association. This book uses psychoanalytic theories and practices to explain how someone like Trump can rise to power, and explores why liberals have failed to provide a convincing or effective political alternative. It will be compelling reading to students and teachers in a range of psychological and political disciplines, and to anyone interested in psychoanalysis and current politics. Robert Samuels teaches writing at the University of California, Santa Barbara, USA. He is also President of UC-AFT, the union representing 4,000 librarians and lecturers (non-tenured faculty) in the UC system, and has authored seven books, including Why Public Higher Education Should Be Free. .